Perceptions of adopters versus non-adopters of a patient portal: an application of diffusion of innovation theory. (2018) - , Srinivas Emani; Peters, Ellen; Desai, Sonali; Karson, Andrew S.; Lipsitz, Stuart R.; LaRocca, Rajani; Stone, John
No abstract available